Threat to arable weeds in Poland in the light of national and regional red lists. - Bomanowska, Anna (Plant Breeding and Seed Science, 2010)
The objective for the study is to present the current threats of arable weeds in Poland. The analysis was conducted on the Polish red lists of arable species (3 national and 22 regional and local) prepared in the period 1994-2008. A total of 105 weeds have been considered as weeds threatened in Poland. All regional and local red lists included a joint total of 184 taxa. The particular regions have between 13 and 95 threatened taxa. The species most frequently appearing in the listings are: Agrostemma githago, Bromus secalinus and Camelina microcarpa. Five taxa (Bromus arvensis, Camelina alyssum, C. sativa, Cuscuta epilinum, Spergula arvensis subsp. maxima) are considered extinct on the national scale, while in the individual regions this number ranges from 1 to 15. A relatively high share is allocated on many regional and local red lists to taxa with an indeterminate level of threat. The conducted comparison shows that there is an urgent need to compile similar listings for the remaining areas of Poland, making it possible to create an updated and real listing of threatened weeds. At the same time, it is necessary to update the existing red lists and to adopt more precise quantitative criteria for the threat estimation, in accordance with the estimation parameters introduced by the IUCN and currently in force...